TINJAUAN HUKUM ISLAM TERHADAP PENGEMBALIAN MAHAR BERGANDA AKIBAT PEMBATALAN PEMINANGAN DALAM (Studi Di Kelurahan Belawan II Kota Medan) - Rahmi Ramadhani; Elsy Renie (Institut Agama Islam Negeri Batusangkar, 2021)
This study examines the tradition of returning multiple dowries due to cancellation of proposal from the perspective of Islamic law in Belawan II Village, Medan City. From these problems, questions arise about how the proposal process is in Belawan II Village, how is the practice of returning multiple dowries due to the cancellation of the proposal and what is the view of Islamic law on the tradition of returning multiple dowries due to the cancellation of the proposal. The type of research that the author uses is a type of field research (field research), to obtain data from the problems studied using qualitative methods. The results of the research that the authors found that the tradition of returning a double dowry due to the cancellation of the proposal in the Belawan II Village, Medan City was carried out by returning the gift at the time of the proposal, namely the gift was in the form of half of the delivery money whose purpose was to be used as a dowry at the time of the marriage contract. Half of the delivery money, which is called the dowry, is returned twice (double) by the woman to the man at the time the proposal has been made. The dowry is returned twice (double) if the cancellation of the proposal is made by the woman. Another sanction is that if the dowry is not returned double (double) at the time of the cancellation of the proposal, neither the man nor the woman may request/accept a proposal from another person, of course this is done by way of deliberation from both parties. The review of Islamic law on the tradition of returning a double dowry due to the cancellation of this proposal is included in the 'urf group.